2002
DOI: 10.1074/jbc.m109034200
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquinone Is Necessary for Caenorhabditis elegansDevelopment at Mitochondrial and Non-mitochondrial Sites

Abstract: Ubiquinone (UQ) is a lipid co-factor that is involved in numerous enzymatic processes and is present in most cellular membranes. In particular, UQ is a crucial electron carrier in the mitochondrial respiratory chain. Recently, it was shown that clk-1 mutants of the nematode worm Caenorhabditis elegans do not synthesize UQ 9 but instead accumulate demethoxyubiquinone (DMQ 9 ), a biosynthetic precursor of UQ 9 (the subscript refers to the length of the isoprenoid side chain). DMQ 9 is capable of carrying out the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 31 publications
5
69
0
Order By: Relevance
“…We observed that homozygous coq-1 animals develop to at least the third larval stage with a few adult escapers. This finding is likely to mean that the coq-1(ok749) mutation results in a maternal effect lethal phenotype in which the first generation of viable offspring progress through larval development with maternally provided CoQ (23). Homozygous coq-1 mutants appear Unc as L3 larvae.…”
Section: Resultsmentioning
confidence: 94%
“…We observed that homozygous coq-1 animals develop to at least the third larval stage with a few adult escapers. This finding is likely to mean that the coq-1(ok749) mutation results in a maternal effect lethal phenotype in which the first generation of viable offspring progress through larval development with maternally provided CoQ (23). Homozygous coq-1 mutants appear Unc as L3 larvae.…”
Section: Resultsmentioning
confidence: 94%
“…This phenotype is likely the most direct consequence of the Q 9 biosynthesis defect of clk-1 mutants, as the wild-type and other long-lived mutant strains have normal growth and reproduction on a Q-deficient food source (10). Thus, the ability to complete growth and produce progeny on Q-deficient E. coli reflects the endogenous Q status of the animal (10,23). Consequently, we assayed the ability of clk-1 maternally rescued animals to complete growth and produce a full brood on a Q 8 -deficient food source.…”
Section: Maternally Rescued Clk-1 Mutants Can Complete Larval Andmentioning
confidence: 99%
“…Reproductive Development When Raised on Q-deficient Bacteria-clk-1 mutants raised on E. coli strains defective in Q 8 biosynthesis arrest development or become sterile, depending on the time of transfer onto the Q-deficient food source (4,10). This phenotype is likely the most direct consequence of the Q 9 biosynthesis defect of clk-1 mutants, as the wild-type and other long-lived mutant strains have normal growth and reproduction on a Q-deficient food source (10).…”
Section: Maternally Rescued Clk-1 Mutants Can Complete Larval Andmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several lines of evidence argue against CoQ depletion accounting for the effects of statins on mitochondria: (i) supplying CoQ to C. elegans conferred no protection from the toxic effects of statins (CoQ 10 was tested at 50 μg/mL and concentrations of CoQ 9 ranging from 10 to 80 μg/mL were tested, all without effect); (ii) the atfs-1(et15) mutant is not resistant to rotenone, antimycin A, or sodium azide, which are inhibitors of the mitochondrial respiratory chain (25,26) (Fig. S7 B-D); and (iii) it is well known that CoQ is dietarily available to C. elegans that are fed Escherichia coli as in our experiments (27,28) and that very little endogenous CoQ is sufficient for a wild-type phenotype even in the absence of dietary CoQ (29).…”
Section: Effects Of Statins On Mitochondria Are Not Related To Inhibimentioning
confidence: 99%